Cover Image. Issue 3 (9th April 2020) - Law, Wallace Boone; Lewis, Megan M.; Ostendorf, Bertram; Hiscock, Peter
Abstract : Cover : The cover image is based on the Research Article Reflecting on siliceous rocks in central Australia: Using advanced remote sensing to map ancient "tool‐stone‐ resources by Wallace Boone Law et al., https://doi.org/10.1002/gea.21776 .